Lexicographic fixation of nationally marked units of minority languages (on the example of electronic dictionaries of Scots and Scottish Gaelic). - Lemeshchenko-Lagoda, Viktoriia; Лемещенко-Лагода, Вікторія Володимирівна (My University, 2023)
ENG :This paper considers the peculiarities of the lexicographic fixation of nationally marked units of minority languages in Scotland, in particular Scots and Scottish Gaelic. The aim of this paper is to analyse dictionary entries and to determine the features of lexicographic rep resentation of nationally-marked units at the microstructural level by identifying common and distinctive features. The source base is represented by such online dictionaries as The Diction aries of Scots Language and Am Faclair Beag. The paper presents a brief overview of the cre ation of dictionaries, which constitute the source base of the research, and also provides a brief overview of their macrostrcture. The common features include the presence of interpretation (translation), transcription and grammatical commentary, while the differences include different formats of illustrating the usage of a lexical item (territorial – in Scottish Gaelic, situational – in Scots). Methods used in the study: general scientific (analysis and synthesis), critical dictionary research, diachronic and synchronic methods.
Лексикографічна фіксація національно-маркованих одиниць мов меншин (на прикладі електронних словників шотландської та шотландсько-гельської мови)
Keywords: dictionary entry; lexicography; microstructure; lexico-graphic process